Polyethylene glycol (PEG)-assisted synthesis of self-assembled cactus-like NH4V3O8 for lithium ion battery cathode. (1st July 2020) - Kou, Lingjiang; Cao, Liyun; Huang, Jianfeng; Song, Jiajia; Feng, Liangliang; Wang, Yong; Chen, Shaoyi; Kajiyoshi, Koji
Abstract: Self-assembled cactus-like NH4 V3 O8 is prepared through polyethylene glycol (PEG)-assisted hydrothermal synthesis method. The samples are characterized by X-ray diffraction and scanning electron microscopy techniques. Adjusting the pH value of the solution can effectively control the morphology of NH4 V3 O8 . The electrochemical measurements indicate that the sample which pH value is 3.7, shows the best cycling performance. It delivers an initial discharge capacity is 228 mAh g −1 and maintains at 156 mAh g −1 under 15 mA g −1 after 50 cycles. The proposed synthetic method can also be developed to address other electrode materials with inferior electronic conductivity and lithium ion diffusion. Graphical abstract: Schematic illustration of cactus-like NH4 V3 O8 by PEG4000-assisted hydrothermal method Image, graphical abstract